Dynamics of sputtered particles in multipulse HiPIMS discharge. (1st April 2023) - Hnilica, J; Klein, P; Vašina, P; Snyders, R; Britun, N
Abstract: The behavior of the ground state neutral and singly ionized atoms is studied in multipulse high power impulse magnetron sputtering processes. The time-resolved two-dimensional laser induced fluorescence was used for imaging the discharge volume (density mapping) during the plasma-on and plasma-off time phases. The role of the number of micropulses and delay time between the micropulses in the pulse package is analyzed and discussed systematically. In addition, the propagation of the sputtered particles from the target is investigated.